Neurobrucellosis and venous sinus thrombosis: an uncommon association - Joana Isabel da Silva Lima; Cátia Filipa Gomes Canelas; Andreia Sofia de Sousa Botelho Trindade Veiga; Dina Maria Mota Carvalho (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: Brucellosis is a commonly diagnosed zoonosis and neurological involvement is rare. A 30-year-old woman presented with a pulsatile headache that was exacerbated by the Valsalva maneuver and refractory to analgesic therapy. The patient also had nausea, cough, and coryza that evolved over 7 days. The neurological examination was unremarkable. Thrombosis of the lateral and sigmoid sinus and ipsilateral internal jugular vein were diagnosed and anticoagulation therapy was started. Brucella spp was identified in a sample of cerebrospinal fluid (CSF); five months after treatment with rifampicin and doxycycline, CSF was sterile. Cerebral venous thrombosis is a very uncommon sign of brucellosis.